Proceedings of the 27th ACM SIGKDD Conference on Knowledge Discovery &Amp; Data Mining 2021
DOI: 10.1145/3447548.3467231
|View full text |Cite
|
Sign up to set email alerts
|

MiniRocket

Abstract: Rocket achieves state-of-the-art accuracy for time series classification with a fraction of the computational expense of most existing methods by transforming input time series using random convolutional kernels, and using the transformed features to train a linear classifier. We reformulate Rocket into a new method, MiniRocket. MiniRocket is up to 75 times faster than Rocket on larger datasets, and almost deterministic (and optionally, fully deterministic), while maintaining essentially the same accuracy. Usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(96 citation statements)
references
References 30 publications
0
96
0
Order By: Relevance
“…The preprocessed data was used as input for MiniRocket [ 13 ] algorithm, a method for time series classification. This method uses random convolutional kernels to transform time series and uses the transformed time series as input for a linear classifier that does the actual prediction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The preprocessed data was used as input for MiniRocket [ 13 ] algorithm, a method for time series classification. This method uses random convolutional kernels to transform time series and uses the transformed time series as input for a linear classifier that does the actual prediction.…”
Section: Methodsmentioning
confidence: 99%
“…There are several state-of-the-art methods for time series classification, such as LSTM-FCN, cBOSS, Proximity Forest, Canonical Interval Forest (CIF), Temporal Dictionary Ensemble (TDE), InceptionTime, Rocket , TS-CHIEF, HIVE-COTE/TDE, etc. MiniRocket authors conducted benchmarks [ 13 , 14 ] with the popular UCR Time Series Classification Archive [ 15 ] datasets, including long time series and datasets with a high number of instances. The authors observed better accuracy than most of the state-of-the-art methods above mentioned.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average age of the seven subjects is 22.4 ± 0.8 years, with the age range of 22-24, and the number of epochs totals to 6955. It includes 3 males, with average age of 22.0 ± 0.0 years and age range (22), and 4 females, with average age of 22.8 ± 1.0 years, and age range of 22-24. The EEG channels are located according to the biosemi128 configuration 1 .…”
Section: A Polysomnographic (Psg) Datamentioning
confidence: 99%